2014
DOI: 10.1111/aos.12542
|View full text |Cite
|
Sign up to set email alerts
|

The gene polymorphisms of UCP1 but not PPAR γ and TCF7L2 are associated with diabetic retinopathy in Chinese type 2 diabetes mellitus cases

Abstract: ABSTRACT.Purpose: This study was designed to investigate the association between the polymorphisms in three insulin resistance-related genes, uncoupling protein-1 (UCP1), peroxisome proliferator-activated receptor c (PPARc) and transcription factor 7-like 2 (TCF7L2) and the susceptibility to diabetic retinopathy (DR) in a Chinese type 2 diabetes mellitus (T2DM) cohort. Methods: A total of 792 patients with T2DM were enrolled and categorized into two groups: (1) the DR group consisted of 448 patients, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…Our study is the first one to demonstrate the rs6060566 of the Romo-1 gene to be associated with DR in subjects with T2DM, as no previous study has been reported to analyse the association of the Romo-1 polymorphism and any phenotype (in this case DR). Our results increase the knowledge of genetic risk factors for developing DR in T2DM (Bhargava et al 2014;Zhang et al 2015). It seems, however, that the retinopathy cases had a more severe form of T2DM in comparison with subjects without DR, that is cases had an earlier onset of diabetes, a longer duration of T2DM and a higher incidence of insulin therapy compared to the subjects without DR. Our findings are in accordance with UKPDS 22 and 50 studies that demonstrated the importance of an earlier onset of diabetes and a longer duration of diabetes (Davis et al 1997;Stratton et al 2001).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Our study is the first one to demonstrate the rs6060566 of the Romo-1 gene to be associated with DR in subjects with T2DM, as no previous study has been reported to analyse the association of the Romo-1 polymorphism and any phenotype (in this case DR). Our results increase the knowledge of genetic risk factors for developing DR in T2DM (Bhargava et al 2014;Zhang et al 2015). It seems, however, that the retinopathy cases had a more severe form of T2DM in comparison with subjects without DR, that is cases had an earlier onset of diabetes, a longer duration of T2DM and a higher incidence of insulin therapy compared to the subjects without DR. Our findings are in accordance with UKPDS 22 and 50 studies that demonstrated the importance of an earlier onset of diabetes and a longer duration of diabetes (Davis et al 1997;Stratton et al 2001).…”
Section: Discussionsupporting
confidence: 45%
“…; Zhang et al. ). It seems, however, that the retinopathy cases had a more severe form of T2DM in comparison with subjects without DR, that is cases had an earlier onset of diabetes, a longer duration of T2DM and a higher incidence of insulin therapy compared to the subjects without DR. Our findings are in accordance with UKPDS 22 and 50 studies that demonstrated the importance of an earlier onset of diabetes and a longer duration of diabetes (Davis et al.…”
Section: Discussionmentioning
confidence: 98%
“…Nicoletti et al [16] analyzed the polymorphic locus of -3826 A>G (rs1800592) in the UCP1 gene and found that it increased the risk of T2DM in obese individuals. Besides that, a study by Zhang et al [31] showed that the allele G and genotype GG of the SNP rs1800592 in the UCP1 gene was associated with the increased risk of proliferative diabetic retinopathy (PDR) in the Chinese population with T2DM. Reasons for the inconsistent results may include: the occurrence and development of diseases are not only associated with the gene but may be modified by lifestyle and environment such as differences in nutritional and economic status.…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs1800592, which is located in the promoter of the UCP1 , has been shown to be associated with glucose homeostasis, adiposity and obesity, as well as changes in the body mass index (BMI) and body weight, resulting from metabolic disorders. UCP 1 has been implicated as a candidate marker for a risk factor of DR and the rs1800592 (c. A-3826G) polymorphism has been associated with PDR [75, 79]. Uncoupling protein 2 (UCP2) regulates production of reactive oxygen species (ROS) by mitochondria.…”
Section: The Other Polymorphisms Modulating Risk Of Drmentioning
confidence: 99%